Multiple positive and negative regulatory elements in the promoter of the mouse homeobox gene Hoxb-4. - Gutman, A (1994)
Mouse Hoxb-4 (Hox-2.6) is a homeobox gene that belongs to a family which also includes Hoxa-4, Hoxc-4, and Hoxd-4 and that is related to the Deformed gene in Drosophila melanogaster. We have determined the sequence of 1.2 kb of 5' flanking DNA of mouse Hoxb-4 and by nuclease S1 and primer extension experiments identified two transcription start sites, P1 and P2, 285 and 207 nucleotides upstream of the ATG initiator codon, respectively. We have shown that this region harbors two independent promoters which drive CAT expression in several different cell lines with various efficiencies, suggesting that they are subject to cell-type-specific regulation. Through detailed mutational analysis, we have identified several cis-regulatory elements, located upstream and downstream of the transcription start sites. They include two cell-type-specific negative regulatory elements, which are more active in F9 embryonal carcinoma cells than in neuroblastoma cells (regions a and d at -226 to -186 and +169 to +205, respectively). An additional negative regulatory element has been delimited (region b between +22 and +113). Positive regulation is achieved by binding of HoxTF, a previously unknown factor, to the sequence GCCATTGG (+148 to +155) that is essential for efficient Hoxb-4 expression. We have also defined the minimal promoter sequences and found that they include two 12-bp initiator elements centered around each transcription start site. The complex architecture of the Hoxb-4 promoter provides the framework for fine-tuned transcriptional regulation during embryonic development.